2019
DOI: 10.1155/2019/2182865
|View full text |Cite
|
Sign up to set email alerts
|

Mulberry Bark Alleviates Effect of STZ Inducing Diabetic Mice through Negatively Regulating FoxO1

Abstract: Dysfunction of insulin secretion and hyperglycaemia were commonly found due to damaged β cells of pancreas. In our previous research, it was found that mulberry branch bark powder (MBBP) was effective in treating diabetes in mice which were induced by STZ and high fat diet. The present study was designed to evaluate the protective effect of MBBP on STZ-induced β cells injury and investigate underlying mechanisms. By preventive administration of branch bark powder, the damage caused by STZ injection was found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…However, the supplementation of hesperidin, diosmin, and the LPE-polyflavonoids remarkably orchestrated the PI3K, p-AKT, FOXO1, and AMPK gene expressions in comparison to those in the diabetic rats. Similar observations were previously demonstrated by Qiu et al [87], who reported that diabetic rats exhibited lower gene expressions of PI3K, p-AKT, and FOXO1 in their pancreatic and liver tissues. It is well known that the mechanism of insulin fundamentally relies on the sequential activations and correlated interactions of the PI3K, p-AKT, and FOXO1 signals to lessen the glucose in blood [88].…”
Section: Discussionsupporting
confidence: 91%
“…However, the supplementation of hesperidin, diosmin, and the LPE-polyflavonoids remarkably orchestrated the PI3K, p-AKT, FOXO1, and AMPK gene expressions in comparison to those in the diabetic rats. Similar observations were previously demonstrated by Qiu et al [87], who reported that diabetic rats exhibited lower gene expressions of PI3K, p-AKT, and FOXO1 in their pancreatic and liver tissues. It is well known that the mechanism of insulin fundamentally relies on the sequential activations and correlated interactions of the PI3K, p-AKT, and FOXO1 signals to lessen the glucose in blood [88].…”
Section: Discussionsupporting
confidence: 91%
“…Te bark from the mulberry branches was scraped, dried, and crushed into powder. Te powder was weighed and blended with a regular diet to get a 10% MBBP diet for mice, which was optimized according to previous research [9].…”
Section: Reagents and Materials Streptozotocin (Stz S0130mentioning
confidence: 99%
“…Mice were randomly assigned to 3 groups: the normal control group (normal), the high-fat diet and STZ injection group (model), and the 10% MBBPtreated group (treated). Te dose of 10% MBBP is the effective dose determined in the previous study [9]. Te mice in the normal group were fed a normal laboratory diet.…”
Section: Animals and The Controlled Dm Modelmentioning
confidence: 99%
See 1 more Smart Citation